2015
DOI: 10.5539/gjhs.v8n6p139
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Pediatric Trauma and Its Patterns in Western Iran: A Hospital Based Experience

Abstract: Background and Objective:Trauma is a major cause of mortality in children aged 1 to 14 years old and its patterns differs from country to country. In this study we investigated the epidemiology and distribution of non-intentional trauma in the pediatric population.Materials and Methods:The archives of 304 children below 10 years old who presented to Taleghani trauma care center in Kermanshah, Iran from March to September 2008, were reviewed. Patients’ demographic and injury related information were registered.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
19
1
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 19 publications
6
19
1
6
Order By: Relevance
“…As reported in previous studies and our study, there were more male pediatric patients than the female 2 , 9 , 12 , 21) , and in particular, THI incidences was most prominent among schoolchildren; the implication is that boys have more physical activities than girls.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…As reported in previous studies and our study, there were more male pediatric patients than the female 2 , 9 , 12 , 21) , and in particular, THI incidences was most prominent among schoolchildren; the implication is that boys have more physical activities than girls.…”
Section: Discussionsupporting
confidence: 83%
“…Falls and traffic accidents account for the majority of injuries in pediatric head trauma 2 , 7 9 , 12 – 14 , 19 – 21) . We found similar results in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the injuries occurred in private homes, accounting for 42.4%, with an additional 25.7% happening in other residential buildings such as apartment complexes. This finding is echoed by Jalalvandi et al in Iran in 2015, who found that 67.4% of traumatic injuries occurred in homes [16] . Similarly, a study in Tanzania by Simon et al in 2013 found that 57.3% of injuries occurred in homes [17] .…”
Section: Discussionmentioning
confidence: 78%
“…Stroke and falling was reported by Mobasheri et al (18), as accidents with high incidence frequency in children. In a study from western Iran, it was demonstrated that falling and traffic accidents were the most frequent accidents in children under six years old (26). Moreover, Lawoyin et al (27) and Ganveer and Tiwari (17) reported falling as the most common accident in children.…”
Section: Discussionmentioning
confidence: 98%